Dekak-Dekak Geometri, Media Pembelajaran Untuk Mengenalkan Bentuk Geometri Pada Anak Kelompok A - Hapsari, Mahda Novita; Ilhami, Baiq Shofa; Agustina, Yulia (Universitas Hamzanwadi, 2019)
This study aims to produce a learning media Dekak-Dekak Geometric to introduce geometric shapes in group A TK Islam Assa’adah NW Kelayu developmental. This development research used the Borg and Gall development model which is carried out in five stages, the needs analysis, the product development and analysis, the product revision, the field testing phase, and the final product revision. The results of this study indicate that the product developed, dekak-dekak geometry was suitable for learning process. Based on the results of the validation of media, dekak-dekak geometry categorized as